Mountain ash : fire, logging and the future of Victoria's giant forests - Lindenmayer, David; Blair, David P.; McBurney, Lachlan; Banks, Sam C. (CSIRO Publishing, 2015)
"Mountain Ash draws together exciting new findings on the effects of fire and on post-fire ecological dynamics following the 2009 wildfires in the Mountain Ash forests of the Central Highlands of Victoria. The book integrates data on forests, carbon, fire dynamics and other factors, building on 6 years of high-quality, multi-faceted research coupled with 25 years of pre-fire insights."--Publisher's description, viewed CSIRO Publishing, 12 November 2015